Pengaruh Teknik Clustering Terhadap Kemampuan Menulis Teks Eksplanasi Siswa Kelas VIII SMP N 4 Medan - Sidabutar, Yuni Katrina (STAI Denpasar Bali, 2023)
This study aims to determine the effect of the clustering technique on the ability to write explanatory texts of class VIII students of SMP N 4 Medan. The population in this study were all class VIII as many as 345 people. The samples taken were class VIII-1 (experimental class) totaling 30 students and class VIII-3 (control class) totaling 30 students. The research method used is an experimental research method with the type of Two Group Post-Test Only Control Design using a quantitative approach. The instrument used is an essay test. The results showed that the ability to write explanatory texts in the control class using conventional techniques was in the less category with an average of 52.7 and did not meet the KKM, while the average value of the experimental class was 80.16 in the good category and met the KKM. Based on the results of the analysis, it was found that the data were normally distributed. After calculating the experimental normality test Lcount < Ltable at a significant level, the post-test data normality test results for the control class were (0.0335 <0.161), the post-test data normality test results for the experimental class were (-0.1358 <0.161). The homogeneity test results for the ability to write explanatory texts are Fcount < Ftable, namely 1.88 < 4.2 and the hypothesis test is tcount > ttable, namely 8.8 > 2.04 , so the null hypothesis (Ho) is rejected and the hypothesis (Ha) is accepted. So, it can be concluded that the application of the clustering technique has an effect on the ability to write explanatory texts of class VIII students of SMP N 4 Medan.